Механізм формування та управління розвитком бізнес-інтегрованих структур у східних регіонах України - Амоша, О.І.; Трушкіна, Н.В.; Шипоша, В.А. (Економічний вісник Донбасу, 2021)
На даний час особливої актуальності набувають проблеми вдосконалення управління розвитком кластерних структур у східних регіонах України з урахуванням європейського досвіду відповідно до сучасних викликів, пов’язаних із смарт-спеціалізацією, модернізацією виробництва та цифровізацією організаційних й управлінських процесів. У зв’язку з цим метою дослідження є обґрунтування теоретичних положень, науково-методичних підходів і розроблення практичних рекомендацій щодо вдосконалення механізму формування та управління розвитком бізнес-інтегрованих структур східних регіонів України. Уточнено суть і зміст термінів «бізнес-інтегрована структура», «розвиток бізнес-інтегрованої структури», «механізм управління розвитком бізнес-інтегрованої структури». Проаналізовано й узагальнено міжнародний досвід розвитку кластерних структур і надано пропозиції щодо його можливого застосування у промислових регіонах України. На підставі узагальнення здійснених досліджень, аналітичних матеріалів дослідницьких і консалтингових компаній, агентств регіонального розвитку, аналізу статистичних даних виявлено основні перешкоди, які стримують ефективний економічний розвиток східних регіонів України. Проаналізовано стратегічні документи щодо соціально-економічного розвитку Донецької та Луганської областей у частині створення кластерних об’єднань. Визначено методичні засади логістичного забезпечення управління розвитком бізнес-інтегрованих структур. Запропоновано та апробовано комплексний підхід до оцінювання ефективності кластерних утворень. Надано пропозиції щодо нормативно-правового регулювання розвитку кластерних структур в економіці України. Обґрунтовано концептуальний підхід до формування кластера як елемента інноваційної інфраструктури промислових регіонів на засадах смарт-спеціалізації. Удосконалено організаційно-економічний механізм функціонування бізнес-інтегрованих структур і запропоновано алгоритм його реалізації на прикладі східних регіонів України. В настоящее время особую актуальность приобретают проблемы совершенствования управления развитием кластерных структур в восточных регионах Украины с учётом европейского опыта в соответствии с современными вызовами, связанными со смарт-специализацией, модернизацией производства и цифровизацией организационных и управленческих процессов. В этой связи целью данного исследования является обоснование теоретических положений, научно-методических подходов и разработка практических рекомендаций по совершенствованию механизма формирования и управления развитием бизнес-интегрированных структур восточных регионов Украины. Уточнены сущность и содержание терминов «бизнес-интегрированная структура», «развитие бизнес-интегрированной структуры», «механизм управления развитием бизнес-интегрированной структуры». Проанализирован и обобщён международный опыт развития кластерных структур и представлены предложения по его возможному применению в промышленных регионах Украины. На основании обобщения проведённых исследований, аналитических материалов исследовательских и консалтинговых компаний, агентств регионального развития, анализа статистических данных выявлены основные барьеры, сдерживающие эффективное экономическое развитие восточных регионов Украины. Проанализированы стратегические документы социально-экономического развития Донецкой и Луганской областей в части создания кластерных объединений. Определены методические основы логистического обеспечения управления развитием бизнес-интегрированных структур. Предложен и апробирован комплексный подход к оценке эффективности кластерных образований. Представлены предложения по нормативно-правовому регулированию развития кластерных структур в экономике Украины. Обоснован концептуальный подход к формированию кластера как элемента инновационной инфраструктуры промышленных регионов на основе смарт-специализации. Усовершенствован организационно-экономический механизм функционирования бизнес-интегрированных структур и предложен алгоритм его реализации на примере восточных регионов Украины. At present, the problems of improving the management of cluster structures in the eastern regions of Ukraine, taking into account the European experience in accordance with modern challenges related to smart specialization, modernization of production and digitalization of organizational and managerial processes, are becoming especially relevant. In this regard, the purpose of the study is to substantiate the theoretical provisions, scientific and methodological approaches and develop practical recommendations for improving the mechanism of formation and management of business integrated structures of the eastern regions of Ukraine. The essence and content of the terms "business integrated structure", "development of business integrated structure", "mechanism for managing the development of business integrated structure" are specified. The international experience of development of cluster structures is analysed and generalized and offers concerning its possible application in industrial regions of Ukraine are given. Based on the generalization of research, analytical materials of research and consulting companies, regional development agencies, statistical analysis, the main barriers that hinder the effective economic development of the eastern regions of Ukraine. Strategic documents concerning the socio-economic development of Donetsk and Luhansk oblasts in terms of creating cluster associations were analysed. Methodical bases of logistical support of management of development of business integrated structures are defined. A comprehensive approach to evaluating the effectiveness of cluster formations is proposed and tested. Proposals on normative-legal regulation of cluster structures development in the national economy of Ukraine are given. The conceptual approach to the formation of the cluster as an element of the innovation infrastructure of industrial regions on the basis of smart specialization is substantiated. The organizational and economic mechanism of functioning of business integrated structures is improved and the algorithm of its realization on the example of the eastern regions of Ukraine is offered. It is proved that the development and implementation of the proposed algorithm for implementing the organizational and economic mechanism of business integrated structures (clusters) will create appropriate conditions for increasing the volume and quality of transport services, intensifying innovative development, as well as implementing a qualitatively new regional model of sustainable development that will meet modern management requirements. Implementation of the developed recommendations for improving the mechanism of formation and management of the development of business integrated structures in Donetsk and Luhansk regions will help to obtain a synergistic effect, the components of which are: economic effect ‒ increasing the level of investment attractiveness of territories; increase of receipts to budgets (regional, local) due to formation of qualitatively new model of regional economy, strengthening of competitive advantages of area and increase of economic capacity of territorial communities in the conditions of decentralization; increase in the volume of cargo transportation and cargo turnover of different types of transport; reduction of costs for the organization of logistics activities by reducing the transport component in the cost of services, reducing the time to perform customs procedures for clearance of goods; ensuring favorable institutional conditions for the functioning of the transport services market; social ‒ job creation and employment growth; ecological ‒ reduction of greenhouse gas emissions from transport due to optimization of transport flows; increasing the level of environmental safety.